Effects of Subthalamic Nucleus Deep Brain Stimulation on Objective Sleep Outcomes in Parkinson's Disease. Issue 2 (6th June 2016) - Amara, Amy W.; Walker, Harrison C.; Joop, Allen; Cutter, Gary; DeWolfe, Jennifer L.; Harding, Susan M.; Standaert, David G.
Abstract: Background: Sleep dysfunction is a common and disabling nonmotor symptom in Parkinson's disease (PD). DBS of the STN improves motor symptoms and subjective sleep in PD, but alternative stimulation parameters to optimize sleep have not been explored. We hypothesized that low‐frequency STN DBS would improve objective sleep more than conventional settings. Methods: Twenty PD subjects with STN DBS (18 unilateral, 2 bilateral) underwent 3 nonconsecutive nights of polysomnography (PSG): DBS off; DBS high frequency (≥130 Hz); and DBS low frequency (60 Hz). Motor symptom tolerability was assessed 30 minutes after resumption of baseline settings the morning following PSG. The primary outcome was change in sleep efficiency between high‐ and low‐frequency nights measured with repeated‐measures analysis of variance. Results: There was no difference in sleep efficiency between nights at high frequency (82.1% [72.6–90.1]) (median [interquartile range]), low frequency (81.2% [56.2–88.8]), or DBS off (82.8% [75.7–87.4]; P = 0.241). Additionally, there was no difference in sleep stage percent, arousals, limb movements, subjective sleep quality, or objective vigilance measures. These outcomes did not change after adjusting for age, sex, disease duration, or side of surgery. No residual adverse motor effects were noted. Conclusions: Although well tolerated, low‐frequency STN DBS did not improve objective sleep in PD. Remarkably, objective measures of sleep were not worse with DBS off. These observations point to the potential for adaptive stimulation approaches, through which DBS settings could be optimized during sleep to meet individual needs. Additionally, these changes could preserve battery life without compromising patient outcomes.